2018
DOI: 10.1080/09540121.2017.1417536
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of HIV treatment cascade in people living with HIV in Saint-Petersburg, Russia

Abstract: The proportion of people living with HIV (PLWH) in need of antiretroviral therapy (ART) is growing rapidly in Russia. Successful treatment outcomes reduces disease progression and contributes to HIV epidemic control. We conducted a pilot study following 100 PLWH newly found eligible for ART in St. Petersburg, Russia. We determined the proportion of PLWH who initiated ART, remained in treatment, and achieved an undetectable VL during 6-month follow up. Semi-structured interviews were conducted prior the initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In addition, common risk factors for TB/HIV co-acquisition in the region are young age, excess alcohol consumption and imprisonment, which are known to lead to poor treatment compliance and retention in care [49]. In a study from Russia, older age and higher education were associated with retention on ART, while a community-based study from St Petersburg demonstrated that the most consistent predictors of poor care engagement and treatment non-adherence were younger age, male gender, recent substance use, including drinking, drug injection and the use of other illicit substances [46,50]. Furthermore, lower medication-taking self-efficacy (belief in own capacity to adhere to HIV treatment) and lower state anxiety were recorded as predictive of reduced adherence, indicating the important role of social, psychological and medical support in improving outcomes [50].…”
Section: Problem 2: Hiv Late Diagnosis and Below Target Art Coverage ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, common risk factors for TB/HIV co-acquisition in the region are young age, excess alcohol consumption and imprisonment, which are known to lead to poor treatment compliance and retention in care [49]. In a study from Russia, older age and higher education were associated with retention on ART, while a community-based study from St Petersburg demonstrated that the most consistent predictors of poor care engagement and treatment non-adherence were younger age, male gender, recent substance use, including drinking, drug injection and the use of other illicit substances [46,50]. Furthermore, lower medication-taking self-efficacy (belief in own capacity to adhere to HIV treatment) and lower state anxiety were recorded as predictive of reduced adherence, indicating the important role of social, psychological and medical support in improving outcomes [50].…”
Section: Problem 2: Hiv Late Diagnosis and Below Target Art Coverage ...mentioning
confidence: 99%
“…Numbers differed widely for countries, from 30% ART coverage in Lithuania to 95% in Uzbekistan [43]. Individual studies based on surveillance data, for instance, from Russia, report even lower ART coverage numbers of around 23%, reiterating the high variability within and between countries [46]. In the TB:HIV cohort covering individual treatment centres, including many university hospitals, PLWH in eastern Europe and central Asia had a higher reported ART coverage, with 72% on ART in 2014, with coverage for individual countries differing from 58% to about 90% [47].…”
Section: Problem 2: Hiv Late Diagnosis and Below Target Art Coverage ...mentioning
confidence: 99%
“…The virus itself, its spread rate, health and economic impact was discussed numerous times by many researchers. Some of their works were used by authors to understand the threat and regional situation (Lebedev et al, 2019;Vetrova et al, 2018;King et al, 2019;Pape, 2018). We also looked at the potential active substances used in the treatment of HIV in Russia (Tremblay et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The medical treatment of HIV is a complex task (Lebedev et al, 2019;Vetrova et al, 2018;Tremblay et al, 2018;Mikhaylov, 2019), thus we gathered the information, referencing to the 32 INNs and their supplements, which were mentioned as the part of the supply order in the documentation of the concluded contracts. These can be found in the list below: Furthermore, the study concentrates on the current and historical market situation, related to the INNs mentioned above.…”
Section: Data Structure and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation